PEMANFAATAN MUSIK BUATAN AI MELALUI DEEPFAKE: STUDI HUKUM KOMPARATIF INDONESIA DAN AMERIKA SERIKAT - Latifatunnisa, Raihani; Ramli, Ahmad M.; Mayana, Ranti Fauza (Fakultas Hukum Universitas Islam Indonesia, 2024)
The advancement of Artificial Intelligence (AI) technology has enabled the creation of music through deepfake methods that realistically mimic the voice, style, and characteristics of artists without their involvement or consent. While this innovation brings new possibilities to the music industry, it also raises significant legal issues, particularly regarding the recognition of AI as an author, the legal protection of AI-generated musical works, and the potential infringement of the original creator’s economic and moral rights. This study aims to examine the legal status and protection of musical works produced by AI using deepfake techniques under Indonesian Law No. 28 of 2014 on Copyright, and to compare it with the legal system of the United States. This research employs a normative juridical method, combining a descriptive-analytical and comparative law approach, with a focus on secondary data derived from primary, secondary, and tertiary legal sources. The findings show that neither Indonesia nor the United States currently recognizes AI as a creator. Copyright protection is only granted if there is a significant human contribution to the creation process. However, Indonesia lacks specific regulations addressing AI, deepfake technology, or objective standards to assess originality and the threshold of similarity, which creates legal uncertainty in enforcing copyright law for AI-generated music.